2008
DOI: 10.3748/wjg.14.6503
|View full text |Cite
|
Sign up to set email alerts
|

Routine rectal retroflexion during colonoscopy has a low yield for neoplasia

Abstract: AIM:To investigate the value of retroflexion in detecting neoplasia in the distal rectum. METHODS:This was a prospective observational study performed in an academic endoscopy unit. Consecutive patients undergoing colonoscopy had careful forward viewing of the distal rectum by retroflexion. Of 1502 procedures, 1076 (72%) procedures were performed with a 140° angle of view colonoscope and 426 (28%) were performed with a 170° angle of view colonoscope. The outcome measurement was the yield of neoplasia in the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 15 publications
1
26
0
2
Order By: Relevance
“…An increase in yield of 8% was demonstrated in one study,33 with others demonstrating a yield of around 2–2.5% 34–37. Manoeuvre success rates between 94%36 and 100%38 have been reported. Retroversion may rarely cause rectal injury39 40 with the estimated the risk 0.01% 41.…”
Section: Rectal Examination and Rectal Retroflexionmentioning
confidence: 86%
“…An increase in yield of 8% was demonstrated in one study,33 with others demonstrating a yield of around 2–2.5% 34–37. Manoeuvre success rates between 94%36 and 100%38 have been reported. Retroversion may rarely cause rectal injury39 40 with the estimated the risk 0.01% 41.…”
Section: Rectal Examination and Rectal Retroflexionmentioning
confidence: 86%
“…It showed how easily an early-stage cancer in a diminutive colonic polyp can be missed when in difficult areas of straight view 3. However, there stands a controversy that RR has a low yield for adenoma detection, causing the risks to surpass the benefits 7,8. For instance, Quallick and Brown9 reported four cases of rectal perforation in the rectum during RR.…”
mentioning
confidence: 99%
“…It is commonly believed that the visualization of the hemorrhoids and the distal rectum might be enhanced by rectal retroflexion [81]. However, in the prospective study by Saad and Rex [82], the authors concluded that routine performance of retroflexion has a very low yield for neoplasia and is not routinely required to achieve a highly effective colonoscopy. In that study with 1,052 patients, 7 polyps were visualized only by retroflexion (6 hyperplastic sessile polyps, one 4-mm sessile tubular adenoma) without any clinical impact.…”
Section: Technical Aspectsmentioning
confidence: 93%